Acceptability and Iron Content of Beanka Crackers (Mung Bean Crackers and Kale Leaf Powder) Potential for Anemia Prevention in Adolescent Girls - Riri Meilani; Ani Intiyati; Fahmi hafid; Taufiqurrahman Taufiqurrahman (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Iron deficiency anemia is a nutritional problem often affecting adolescent girls, leading to decreased concentration, fatigue, and developmental disorders. This study aimed to evaluate the acceptability and iron content of Beanka Crackers as an alternative nutritious snack for anemia prevention. An experimental design with three formulations was used: BKC0 (75 g wheat flour), BKC1 (45 g wheat flour, 25 g mung bean flour, 5 g kale leaf powder), and BKC2 (30 g wheat flour, 35 g mung bean flour, 10 g kale leaf powder). Acceptability was tested with 30 panelists using a hedonic scale to assess color, taste, aroma, and texture. Iron content was analyzed with Atomic Absorption Spectroscopy (AAS). Data were evaluated using the Kruskal-Wallis and Mann-Whitney tests. Results showed significant differences (p < 0.05) in color, taste, and texture, but not aroma. BKC1 achieved the highest overall acceptability (3.84) and texture score (4.07), compared with BKC0 and BKC2. BKC1 also contained the highest iron concentration at 0.0457 mg/g. In conclusion, BKC1 demonstrated the best acceptability and potential as an iron-rich snack for adolescents. Further product refinement is recommended to enhance sensory quality and strengthen its application as a functional food for anemia prevention.